PANORAMA DO RADIOJORNALISMO NAS EMISSORAS RADIOFÔNICAS DO SUL DO MARANHÃO - MAPEAMENTO, ROTINAS PRODUTIVAS E PRODUTOS JORNALÍSTICOS - Brito, Nayane Cristina Rodrigues de (2017)
The radio has a comprehensive performance in the South of Maranhão, in itself it is verified that, in about 70% of the cities located around this geographic region, there is one or more radio stations with local programming. Thus, the events of the region and locality reach a large part of the population, mainly through this media, taking into consideration that 29% of the population live in the countryside. Given this data, the following question arises: What is the panorama of radio journalism in the South of Maranhão? This paper approaches this issue to reach the objective of drawing a panorama of the radio journalistic production in the South of Maranhão, from the observation of productive routines of radio stations and analysis of radio products, to record and understand the contemporary radio journalistic practices in the South of Maranhão. The research chose different methodological strategies in order to contribute with the results for this paper. The first stage of the master’s degree research, based on the conceptions related to the theoretical bias of Geografias da Comunicação (MOREIRA, 2012), consisted in mapping the existence of radio transmitters with radio waves in the cities of the South of Maranhão and, in those, what is broadcast. In consonance with the results of this mapping, the productions of some radio stations were submitted to analyzes of their production routines and their respective final productions in consonance, with objective of verifying the function and importance of local radio journalism. In this second stage of research, carried out from May 28th to August 26th of 2016, the methodological procedures of newsmaking are incorporated with collaboration of methodological strategies of ethnography. A total of 27 productions were broadcast on Marconi FM Radio in Açailândia; Nativa FM Radio, located in Imperatriz; from the city of Barra do Corda, Rio Corda FM Radio; Located in Balsas, Boa Notícia AM Radio; following, Cidade FM Radio, in Fortaleza dos Nogueiras; Aliança FM Radio, heard in Grajaú and, finally, Fronteira FM Radio, from Itinga – Maranhão. After the field insertion, with dense descriptions of the routine produced by the seven radios mentioned and an audio file of two accompanied programs, we had the analysis of the journalistic product with focus on the radiophonic language, from the strategic Analyzes of Content in Journalism. In order to measure the frequency of content, from the analysis categories, seven programs were selected, one from each radio station: "Marconi Cidade", from Marconi FM Radio; "Rádio Alternativo", verified by Nativa FM Radio; "Jornal Central Cortina de Noticias", broadcast by Rio Corda FM Radio; "Conversando com a Comunidade", heard through Cidade FM Radio; "Rádio Notícia" of Alliance FM Radio; "Momento do Esporte", broadcast by Fronteira FM Radio and "Radar 770", accompanied by Boa Notícia Radio. The results obtained show a mapping of the radio with 61 stations in South of Maranhão. As for radio journalism, news production is inferior to the reproduction of information on websites, blogs, radio news agencies, WhatsApp, among others. A situation marked directly in the dynamic of the operation of the stations, with few professionals for the work of calculation.